Preacher. The final season [videorecording (Blu-Ray)]. - Gilgun, Joe, 1984-; Cooper, Dominic, 1978-; Negga, Ruth, 1982- (Sony Pictures Home Entertainment, 2020)
As the show inches closer to the finale, God's endgame for the universe begins to click into place. Trapped between heavenly prophecies, hellish prisons, and all-out nuclear war, Jesse, Tulip, and Cassidy make their bloody way to the Most High. Whether they can reach God in time, or whether all this carnage is part of His divine plan, will soon be revealed as it barrels towards the end of the world.